Happiness, economic well-being, social capital and the quality of institutions - Mota, Gabriel Leite (2010)
Since Jeremy Bentham, utilitarians have argued that happiness, not just income or wealth, is the maximand of individual and social welfare. By contrast, Rawls and followers argue that to share a common perception of living in a just society is the "ultimate good" and that individuals have a moral ability to evaluate just institutions. In this paper we argue that just institutions, apart from their intrinsic value, also have an instrumental value, both in economic performance and in happiness. Thus happiness -- or subjective well being -- is analyzed as being a function of economic well-being, the quality of public institutions and social ties. Cross section individual data from citizens in OECD countries show that income, education and the perceived quality of institutions have the highest impact on life satisfaction, followed by social capital. Country analysis shows a non linear but positive influence of per capita GDP on life satisfaction, but also that unemployment and inflation reduce average happiness, the former effect being stronger. Finally, better quality public institutions and having more social capital also bring more happiness. We conclude with some policy implications.